The impact of electronic nicotine delivery systems on adolescent respiratory health: A review of the HKSAR situation - Jason Chi Shing Law (Pediatric Respirology and Critical Care Medicine)
Electronic nicotine delivery systems (ENDS) have rapidly gained popularity among adolescents worldwide, leading to concerns about their impact on respiratory health. This review examines evidence on ENDS use among adolescents in the HKSAR (Hong Kong) and its effects on respiratory health, current regulations, and public health implications and strategies. ENDS heat nicotine solutions to produce inhaled aerosols. While marketed as safer alternatives to cigarettes, their safety and efficacy are unestablished. ENDS adoption among Hong Kong adolescents has risen despite reduced smoking prevalence. Studies globally link ENDS to acute respiratory effects like airway inflammation and impairment. Long-term risks include lung irritation, hypersensitivity, and future COPD. ENDS use is associated with more respiratory symptoms versus never-use. Regulation in Hong Kong prohibits ENDS sales and ads, but possession and use is not illegal. Challenges include unclear product sources and public use normalising adolescent uptake. Potential public health strategies include education campaigns, interventions to curb initiation and promote cessation, and expand smoke-free zones. Future research should continue monitoring ENDS use patterns among Hong Kong adolescents and interventions tailored to this population. As ENDS risks likely outweigh benefits for youth, ongoing efforts to reduce uptake are needed to address this major public health concern.